2003
DOI: 10.1029/2002ja009711
|View full text |Cite
|
Sign up to set email alerts
|

Planetary bow shocks: Gasdynamic analytic approach

Abstract: [1] A new analytical model of the bow shock surface is suggested for reasonably accurate and fast prediction of this boundary's position near obstacles of different shape. For axially symmetric obstacles the model was verified by comparison with experiments and results of gasdynamic code application for a wide range of upstream polytropic indexes, 1.15 < g < 2, and Mach numbers, 1 < M s < 1. The model can also be used for prediction of the bow shock position around nonaxially symmetric obstacles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…related (at least in an isothermal atmosphere), causing underestimation/overestimation of the Mach number from the value of ∆/R assuming the reference model (e.g. Verigin et al 2003). Moreover, we see that the combination of the two effects produces an even larger deviation than the linear sum of the deviations expected from each effect separately.…”
Section: Acceleration/deceleration Plus Density (Pressure) Gradientsmentioning
confidence: 74%
See 2 more Smart Citations
“…related (at least in an isothermal atmosphere), causing underestimation/overestimation of the Mach number from the value of ∆/R assuming the reference model (e.g. Verigin et al 2003). Moreover, we see that the combination of the two effects produces an even larger deviation than the linear sum of the deviations expected from each effect separately.…”
Section: Acceleration/deceleration Plus Density (Pressure) Gradientsmentioning
confidence: 74%
“…The theory of bow shocks driven by blunt bodies has been extensively studied theoretically and experimentally, including space physics applications (e.g. Van Dyke 1958;Farris & Russell 1994;Fairfield et al 2001;Petrinec 2002;Verigin et al 2003;Keshet & Naor 2016). The standoff distance ∆ is defined as the distance between the stagnation point of the body and the closest point on the shock front (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a highly dynamic boundary, controlled by temporal variations in solar wind characteristics. The general shape of the shock has been investigated with empirical models [e.g., Fairfield, 1971;Slavin and Holzer, 1981], gas dynamic flow models [e.g., Slavin et al, 1983a;Verigin et al, 2003a], and magnetohydrodynamic models [e.g., Chapman and Cairns, 2003] and is well described by a conic section. Formisano et al [1971] found that the subsolar bow shock position moves outward during conditions of low Alfvén Mach number (M A ).…”
Section: Introductionmentioning
confidence: 99%
“…Maloney & Gallagher (2011) examined whether normalized stand-off distance ratios, which are defined as Δ CME divided by either the CME radius (R CME ) or the radius of curvature at the nose of a CME front ( ) R C CME , are in agreement with those from bow shock relationships based on gasdynamic (GD) theories (Seiff 1962;Spreiter et al 1966;Farris & Russell 1994). For this, they analyzed the CME-driven shock observed on 2008 April 5 by COR2 and the Heliospheric Imager 1 (H1) of the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI; Howard et al 2008) on board the Solar TErrestrial Relations Observatory (STEREO) A and B, and determined the normalized stand-off distance ratios by using the tie-point method (Temmer et al 2009;Byrne et al 2010;Mierla et al 2010) and the analytical bow shock model (Verigin et al 2003). They found that stand-off distance ratios D ( ) R CME CME show better agreements with the relationships using the ratio of specific heat (γ) of 5/3 than normalized stand-off distances Using bow shock relationships under magnetohydrodynamic (MHD) theories (Cairns & Lyon 1995, 1996Merka et al 2003) and the relationships under GD theories, several researchers made an observational test as to which bow shock relationship is better suited for predicting Earth's bow shock locations (Fairfield et al 2001;Merka et al 2003).…”
Section: Introductionmentioning
confidence: 99%